Analysis of renin-angiotensin-aldosterone system gene polymorphisms in resistant hypertension - S.R.S. Freitas (Brazilian Journal of Medical and Biological Research, 2007)
Essential hypertension is a disease multifactorially triggered by genetic and environmental factors. The contribution of genetic polymorphisms of the renin-angiotensin-aldosterone system and clinical risk factors to the development of resistant hypertension was evaluated in 90 hypertensive patients and in 115 normotensive controls living in Southwestern Brazil. Genotyping for insertion/deletion of angiotensin-converting enzyme, angiotensinogen M235T, angiotensin II type 1 receptor A1166C, aldosterone synthase C344T, and mineralocorticoid receptor A4582C polymorphisms was performed by PCR, with further restriction analysis when required. The influence of genetic polymorphisms on blood pressure variation was assessed by analysis of the odds ratio, while clinical risk factors were evaluated by logistic regression. Our analysis indicated that individuals who carry alleles 235-T, 1166-A, 344-T, or 4582-C had a significant risk of developing resistant hypertension (P < 0.05). Surprisingly, when we tested individuals who carried the presumed risk genotypes A1166C, C344T, and A4582C we found that these genotypes were not associated with resistant hypertension. However, a gradual increase in the risk to develop resistant hypertension was detected when the 235-MT and TT genotypes were combined with one, two or three of the supposedly more vulnerable genotypes - A1166C (AC/AA), C344T (TC/TT) and A4582C (AC/CC). Analysis of clinical parameters indicated that age, body mass index and gender contribute to blood pressure increase (P < 0.05). These results suggest that unfavorable genetic renin-angiotensin-aldosterone system patterns and clinical risk variables may contribute to increasing the risk for the development of resistant hypertension in a sample of the Brazilian population.